Improving Achievement Through Long Jump Courses With The TGT Method For STOK Bina Guna Students - Eka Abdurrahman; Jonathan Aprilo Utodam Silaban; Alfin Paulus Maruli Sirait; Rizky Putra; Ignasia Br Ginting; Yongki Fardila; Gardner Paulus Sinaga; Emanuel Perlindungan Daeli (Journal Physical Health Recreation (JPHR), 2025)
This study aims to improve the achievement of long jump lectures in first semester STOK Bina Guna students through the TGT method. This study uses classroom action research, where the study uses a triangulation assessment system. The study was conducted in two cycles, consisting of planning, implementation, observation and reflection of actions for each cycle. The subjects of the study were 30 first semester STOK Bina Guna students. The data source for this study came from attendance data obtained from the Head of the STOK Bina Guna PJKR Study Program. Data collection techniques used tests and measurements of long jump abilities and observations from the training process. descriptive analysis techniques based on qualitative and quantitative analysis in accurate data processing. The results of the study indicate that the method of improving achievement through TGT can improve students' long jump achievements from the pre-cycle to cycle I and from cycle I to cycle II. From the data analysis, the results obtained in cycle I showed an increase in long jump learning outcomes in students who completed as many as 22 students. While in cycle II, the increase in long jump achievement was 27 students who completed. The conclusion of this classroom action research is that through the application of the TGT method, long jump learning outcomes can be improved for STOK Bina Guna students.